2010
DOI: 10.1128/jvi.00533-10
|View full text |Cite
|
Sign up to set email alerts
|

The Clinically Approved Proteasome Inhibitor PS-341 Efficiently Blocks Influenza A Virus and Vesicular Stomatitis Virus Propagation by Establishing an Antiviral State

Abstract: Recently it has been shown that the proinflammatory NF-B pathway promotes efficient influenza virus propagation. Based on these findings, it was suggested that NF-B blockade may be a promising approach for antiviral intervention. The classical virus-induced activation of the NF-B pathway requires proteasomal degradation of the inhibitor of NF-B, IB. Therefore, we hypothesized that inhibition of proteasomal IB degradation should impair influenza A virus (IAV) replication. We chose the specific proteasome inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 78 publications
3
34
1
Order By: Relevance
“…Similarly, others have shown antagonism in vitro in other cell types as well. Specifically, Neznanov et al found that bortezomib inhibits VSV protein synthesis via stimulation of stress-related processes in HeLa cells [40], and Dudek et al reported that bortezomib activates NF-κB, resulting in an antiviral state that ultimately inhibits VSV propagation in A549 adenocarcinoma cells [39]. However, unlike the results reported by Dudek, we show that bortezomib does not activate but inhibits NF-κB in myeloma cells (Figure 3).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Similarly, others have shown antagonism in vitro in other cell types as well. Specifically, Neznanov et al found that bortezomib inhibits VSV protein synthesis via stimulation of stress-related processes in HeLa cells [40], and Dudek et al reported that bortezomib activates NF-κB, resulting in an antiviral state that ultimately inhibits VSV propagation in A549 adenocarcinoma cells [39]. However, unlike the results reported by Dudek, we show that bortezomib does not activate but inhibits NF-κB in myeloma cells (Figure 3).…”
Section: Discussioncontrasting
confidence: 78%
“…We show that bortezomib and VSV are antagonistic in myeloma cell lines and that bortezomib inhibits VSV replication and spread in these cells. Similarly, antagonism between bortezomib and VSV has been reported in vitro in other cell types as well [39, 40]. In vivo , however, using two syngeneic, immunocompetent mouse myeloma models, we found that bortezomib does not affect intra-tumoral VSV titers and that this drug actually enhances tumor reduction when compared to single-agent VSV treatment.…”
Section: Introductionsupporting
confidence: 75%
“…This effect is thought to be due to the induction of C/EBPβ, a cellular transcription factor that can then initiate the activation of EBV lytic gene expression (31). While bortezomib has been shown to increase EBV replication, other studies have also found that bortezomib inhibits VSV via activation of NF-κB, resulting in an antiviral state that ultimately inhibits VSV propagation (32). Consistent with these reports, treatment of myeloma cells with bortezomib was was found to inhibit VSV replication and show less than additive cell killing in vitro (33).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the proteasome inhibitor drug bortezomib, or PS-341, which activates the NF-jB pathway through degradation of IjB, also inhibits IAV replication. Bortezomib is a clinically approved anticancer drug and has been demonstrated to exert antiviral activity by upregulating the expression of antiviral genes such as interleukin 6 and MxA [184]. Therefore, both inhibitors and activators of the NFjB pathway can serve as potential antivirals.…”
Section: Host Cellular Factors As Anti-influenza Targetsmentioning
confidence: 99%